Symmetric dimethylarginine concentrations in dogs with hypothyroidism before and after treatement with levothyroxine. (14th September 2020) - Di Paola, A.; Carotenuto, G.; Dondi, F.; Corsini, A.; Corradini, S.; Fracassi, F.
Abstract : Objectives: To evaluate the serum symmetric dimethylarginine (SDMA) and serum creatinine concentrations in a population of hypothyroid dogs at the time of diagnosis and after treatment. Materials and Methods: Serum SDMA and serum creatinine were measured in serum samples of 24 healthy dogs and 24 hypothyroid dogs, at the time of diagnosis (T0) and after supplementation with levothyroxine (T1). Results: The mean SDMA concentrations (reference intervals [RI] <18 μg/dL and <14 μg/dL depending on the source) were 11.7 ± 3.5 μg/dL, 13.8 ± 3.1 μg/dL and 11.83 ± 2.87 μg/dL in healthy dogs, and in the hypothyroid dogs at T0 and T1, respectively. The SDMA concentrations were higher in the hypothyroid dogs at T0 in comparison with the healthy dogs. Of the hypothyroid dogs, 1 out of 24 had an SDMA concentration above 18 μg/dL and 12 out of 24 above 14 μg/dL at T0. At T1, none of the hypothyroid dogs had SDMA concentrations above 18 μg/dL and two of them had SDMA concentrations above 14 μg/dL. The serum creatinine concentration was higher in the hypothyroid dogs at T0 as compared to the healthy dogs. At T0, 8 out of 24 hypothyroid dogs had serum creatinine concentrations above the RI (>1.4 mg/dL). In all but one dog, serum creatinine normalised after treatment. Clinical Significance: The SDMA and serum creatinine concentrations were higher in hypothyroid dogs at diagnosis as compared to healthy dogs. Serum creatinine concentrations were increased in one‐third of the hypothyroid dogs and in the majority of cases normalised after levothyroxine supplementation. SDMA concentrations were rarely above the upper limit of the RI when the higest (<18 μg/dL) cut‐off was employed. The diagnostic accuracy of SDMA in dogs with thyroid dysfunction requires additional evaluation.